Pandemic and vaccine coverage: challenges of returning to schools - Ana Paula Sayuri Sato (Universidade de São Paulo, 2020)
ABSTRACT Since March 2020, Brazil has faced the pandemic of the coronavirus disease 2019 (Covid-19), which has severely modified the way in which the population lives and uses health services. As such, face-to-face attendance has dropped dramatically, even for child vaccination, due to measures of social distancing to mitigate the transmission of the virus. Several countries have recorded a substantial drop in vaccination coverage in children, especially of those under two years of age. In Brazil, administrative data indicate the impact of the covid-19 pandemic on this downward trend, which was already an important challenge of the National Immunization Program in recent years. Many children will be susceptible to immunopreventable diseases, which reinforces the need to assess the vaccine status of schoolchildren before returning to face-to-face classes.